THE IMPACT OF THE SPECIAL AUTONOMY FUND ON THE CONVERGENCE OF THE HUMAN DEVELOPMENT INDEX IN ACEH - Safwadi, Irwan (SCAD Independent, 2020)
Since 2008, district/city governments in Aceh have received special autonomy funds transfers from the central government.  This study aimed to assess the absolute and conditional convergence of HDI in Aceh, and examine the effect of special autonomy funds and other socio-economic variables on HDI conditional convergence during the implementation of special autonomy in Aceh. The data used were secondary data with panel data covering 23 districts/cities in Aceh in 2008-2017. The analysis model used was the convergence model with the Fixed Effect panel regression analysis approach; testing analytical tools used the Hausman Test, Chow Test, and statistical tests. The regression results of the fixed effect model revealed that the occurrence of absolute HDI convergence in districts/cities in Aceh. The estimation of conditional convergence indicated that population density played a significant and significant role in driving the convergence of HDI districts/city. Special autonomy funds had a positive influence but were not significant to encourage the HDI convergence process. It was also followed by the number of working people who did not significantly influence the HDI.  Therefore, policymakers in districts/cities in Aceh must continue to pay serious attention in an effort to accelerate human development, through human development priorities sourced from Aceh's special autonomy fund.